Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.